Search for exclusive b→u semileptonic decays of B mesons - BEAN, A.; et al. (Institutional Knowledge at Singapore Management University, 1993)
Using a sample of 935 000 BB¯ pairs collected with the CLEO-II detector at the Cornell Electron Storage Ring, we have obtained upper limits on the branching ratios for the b→ul−ν¯ processes B−→ωl−ν¯, B−→ρ0l−ν¯, and B¯0→ρ+l−ν¯. The combined result using the relationships among the widths for these three modes is B(B−→ρ0l−ν¯)